1998
DOI: 10.1007/s004320050148
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of concomitant multiple low-dose doxorubicin and thoracic irradiation on ex vivo cardiac performance of the rat heart

Abstract: The effects of doxorubicin alone or combined with local heart irradiation on ex vivo cardiac performance were studied in Sprague-Dawley rats. Rats were treated with doxorubicin either administered as a single bolus injection or administered weekly during a period of 10 weeks. In "combined" experiments, local heart irradiation with a single dose of 15 Gy was given prior to drug administration. Evaluation of cardiac performance was performed 14 weeks after initiation of treatment. At drug doses that were tolerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Little is known about a possible interaction between anthracyclines and radiation on cardiovascular damage. There are some indications from rat studies that the interaction between doxorubicin and local heart irradiation is additive when the treatments are given concomitantly (Wondergem et al, 1998). Several clinical studies showed that anthracycline-containing therapy may further increase the radiation-related risk of congestive heart failure and valvular disorders two-to three-fold compared with radiotherapy alone (Moser et al, 2006;Aleman et al, 2007); this effect may be more than additive .…”
Section: Anthracyclinesmentioning
confidence: 99%
“…Little is known about a possible interaction between anthracyclines and radiation on cardiovascular damage. There are some indications from rat studies that the interaction between doxorubicin and local heart irradiation is additive when the treatments are given concomitantly (Wondergem et al, 1998). Several clinical studies showed that anthracycline-containing therapy may further increase the radiation-related risk of congestive heart failure and valvular disorders two-to three-fold compared with radiotherapy alone (Moser et al, 2006;Aleman et al, 2007); this effect may be more than additive .…”
Section: Anthracyclinesmentioning
confidence: 99%
“…Doxorubicin is applied in myeloblastic leukaemia, lymphoblastic leukaemia (Wondergem et al 1998;Ibrahim et al 1999), breast cancer (Nielsen et al 2000), ovarian tumour, urinary bladder cancer, small-cell lung tumour, bone and soft tissue sarcoma, lymphomas and thyroid and stomach cancer treatment (Gnewuch & Sosnovsky 2002). After intravenous injection, the antibiotic quickly disappears from the plasma, which indicates a dynamic distribution of doxorubicin to the organs and tissues.…”
Section: The Characteristics Of Selected Drugs Causing Multidrug Resimentioning
confidence: 99%
“…Radiation therapy to the mediastinum (Wondergem et al 1998), advanced age and pre-existing cardiac disorders (Ibrahim et al 1999) augment the cardiotoxicity. To increase the safety of doxorubicin, combination with other drugs has been investigated (Herman et al 2000).…”
Section: The Characteristics Of Selected Drugs Causing Multidrug Resimentioning
confidence: 99%
See 1 more Smart Citation